A literature review on the state and practice of life cycle cost (LCC) in Malaysia - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2011)
Commentators suggest that most clients focus only on initial or capital costs but very seldom they consider future costs (maintenance, replacement, etc) when they initiate and procure building and infrastructure facilities. In addition, techniques including Life Cycle Cost (LCC) were seldom applied; these despite the fact that past research indicated that the application of such techniques could provide clients with a holistic view on the total costs (initial, maintenance, replacement, etc) of their proposed development. Consequently, a research project aimed at investigating the state and practice of LCC in Malaysia was initiated and carried out. This paper reports on the initial stage of the study and its outcome. The initial study was conducted through a comprehensive review of literature on LCC in general and specifically on the practice of LCC in Malaysia. The outcome of the initial study suggests that among others; most clients and their consultants are aware of the concept and practice of LCC, there exist several models and techniques on how to apply LCC for building and infrastructure projects and yet LCC is seldom practiced in Malaysia. The findings provide current information on the state and practice of LCC in Malaysia.